Tekst w kulturze, kultura w tekście. Tradycja łacińska i literatura staropolska w "Spowiedzi" Calka Perechodnika - Skwara, Marek (My University, 2013)
The article analyses and interprets the apothegms and quotations from ancient and old-Polish literature in one of the most important testimonies of the Holocaust in world literature. In Polish criticism, there are few discussions of Perechodnik’s journal, and the existing articles are controversial because of their biased interpretations, which, in the present author’s opinion, are often manipulatory. It seems that the Polish intepretators of "Spowiedź" try, contrary to the author’s clear intention, to inscribe the text in the current controversies between Poles and Jews, while disregarding the third nation (Germans), and to turn Perechodnik into a postmodern author, because it allows for suspension of ethical rules. The greatness and tragedy of the author, however, stand for their own without such manipulations.
Text in Culture, Culture in Text. The Latin Tradition and Old-Polish Literature in Calek Perechodnik’s "Spowiedź" [Confession]
Keywords: Holocaust; journal; Polish-Jewish-German relations during the Holocaust; manipulations; Latin and Old-Polish tradition; apothegm and proverb